Phenotypes regulated by N-acyl homoserine lactones in Salmonella enterica - Freitas, Leonardo Luiz de (2021)
Quorum sensing (QS) is a bacterial communication system mediated by signaling molecules that allow a microbial community to regulate a set of genes in a coordinated way. Different mechanisms of cell-cell communication have been described in bacteria that infect humans, including Salmonella. In this pathogen, the QS mediated by autoinducer 1 (AI-1), also known as acyl homoserine lactones (AHLs), is incomplete due to the absence of proteins (LuxI or homologous) responsible for the synthesis of these molecules. However, Salmonella has the SdiA protein, homologous to the LuxR protein, which allows it to recognize and respond to AHLs synthesized by other bacteria or added to the culture medium. The elucidation of Salmonella virulence mechanisms regulated by AHLs may contribute to the development of strategies to control this pathogen. Thus, the aims of the present study were to investigate the function of the quorum signaling molecule, N-dodecanoyl homoserine lactone (C12-HSL), in regulating virulence genes and general stress response, resistance to nisin bacteriocin and acid stress, as well as to evaluate the influence of C12-HSL on the virulence of Salmonella Enteritidis PT4, using Galleria mellonella larvae. In this study, the effect of extracts from the culture medium of Rahnella inusitata containing AHLs on the adhesion and motility of Salmonella was also evaluated. Salmonella cells cultured in anaerobiosis at 37 °C in the presence of 50 nM C12-HSL increased the expression of the phoP, phoQ, pmrA, and pmrB genes that are directly involved with stress resistance, as well as increased nisin resistance and to acid stress. Changes in cell membrane fatty acids and cell surface charge may have contributed to the survival of the pathogen under stress conditions and in the reduction of leakage of NADPH and potassium ions. Cultivation in the presence of C12-HSL also increased the expression of the rpoS, arcA, arcB, and invA genes and the virulence of Salmonella inoculated in the G. mellonella hemolymph, resulting in higher larval mortality, in addition to increasing Salmonella survival in the hemolymph and within the hemocytes. G. mellonella inoculated with Salmonella grown in the presence of C12-HSL increased the production of pigment, nitric oxide, antioxidant enzymes, caspases-3 and LC3 in this model of infection. The presence of R. inusitata extracts containing AHLs increased the adhesion of Salmonella in stainless steel coupons and motility. The demonstrated evidence that greater resistance to stress and virulence in Salmonella Enteritidis PT4 are regulated by AHLs reinforce the need to deeply understand the function of these signaling molecules in this pathogen, considering its importance as an agent of foodborne diseases and responsible for thousands of deaths annually. Keywords: Salmonella. Quorum sensing. N-acyl homoserine lactones. Virulence. Stress resistance.